Assessment of Blood Pressure in Primary Monosymptomatic Nocturnal Enuresis - Yousefichaijan, Parsa; Khosrobeigi, Ali; Taherahmadi, Hassan; Soltani, Manoochehr; Ghandi, Yazdan; Shariatmadari, Fakhreddin; Bayat, Somaye; Alinejad, Saeed; Hashemi, Mojtaba; Arjmand, Ali (Journal of Pediatric Nephrology, 2016)
Introduction: Enuresis is defined as the repeated voiding of urine into bed at least twice a week for at least 3 consecutive months in a child who is at least 5 years of age. Primary enuresis occurs in children who have never been consistently dry through the night. Monosymptomatic enuresis has no associated daytime symptoms. Increased nocturnal urine production in primary nocturnal enuretic patients could possibly be associated with autonomic nervous system dysfunction. The aim of this study was to investigate autonomic nervous system function in enuretic children. Materials and Methods: In this study, children with monosymptomatic primary nocturnal enuresis (MPNE) and healthy children without MPNE were enrolled and their blood pressure was measured twice a day (in the morning and afternoon). Urinalysis, urine electrolyte levels, urinary culture, and urinary system ultrasound were performed in all the children. They were also requested to have a diary about daily fluid intake and the volume of daily urine. Results: The MPNE group comprised 100 children (M/F: 58/42) and the control group included 100 healthy children (M/F: 51/49). The mean age of the children was 8.1±2.3 and (8.9±2.53 years in MPNE and control groups, respectively. The mean diastolic blood pressure (DBP) during the nighttime and daytime did not differ between the groups (p-value>0.05); however, the mean systolic blood pressure (SBP) was significantly higher in the nighttime in the MPNE group (p-value<0.05) but did not differ between the groups during the daytime (p-value>0.05). Conclusions: Nighttime SBP was significantly higher in children with MPNE. These subtle abnormalities of the circadian blood pressure regulation may reflect autonomic nervous system dysfunction and contribute to the pathogenesis of MPNE. Keywords: Child; Enuresis; Blood pressure; Autonomic dysfunction